Optimization of enzymatic extraction of stevioside from stevia rebaudiana leaves by using cellulase - Siti Sarah , Abdullah (2013)
Stevioside is one of the components known as diterpene glycoside existing in Stevia rebaudiana leaves which have 250 to 300 sweeter than sucrose at the concentration of 0.4% (w/v). It is used as sweetening agents and taste modifier mostly in food industry. Moreover, stevioside has no calorific value and suitable used in therapeutic especially in treating diabetic people. The objective of this research is to optimize the extraction of stevioside from Stevia rebaudiana leaves by using the cellulase. A Central Composite Design (CCD) has been chosen to study the effect of enzyme concentration, incubation time and temperature on extraction of stevioside. The medium for enzyme used is acetate buffer while ethanol is applied as solvent in the enzymatic extraction of stevioside by performing various parameters such as concentration of enzyme, incubation time and temperature. The p-value for cellulase concentration and incubation time was less than 0.05 indicate that these factors have significant effects on the extraction yield of stevioside. The extraction of stevioside is represented by a quadratic model with p-value <0.0001. From the experimental work, an enzymatic extraction method gives the highest concentration of stevioside (840.839 μg/ml) at 45°C as maximum temperature, concentration of cellulase at 1.75% (w/v) and the incubation times of 105 minutes gives the maximum time required to complete the extraction process of stevioside. The extraction stevioside yield in this experiment gets more than predicted values (835.49μg/ml). However the experimental value is not much difference compare to the predicted value. The extraction of stevioside from Stevia rebaudiana leaves using cellulase is a new efficient way of obtaining high concentration of stevioside and can minimize the use of solvent and energy consumption in degrading the cell wall